Identification of Mercury Levels and Disease Symptoms in Workers at Traditional Gold Mining Sites in the Working Area of Public Health Centre Ujung Padang Rasian - Lensoni; Wildan Seni; Murni Yanti; Yuni Agnes Lubis; Heri Setiawan; Taufiq Karma (Poltekkes Kemenkes Surabaya, 2024)
This research aims to identify the symptoms of diseases experienced by gold mine workers due to mercury exposure in the Public Health Centre Ujung Padang Rasian work area, South Aceh Regency, Aceh Province. This study used a cross-sectional approach involving 39 respondents, and mercury levels were analyzed using an Atomic Absorption Spectrofotometry (AAS) instrument. Based on the research findings, most workers experienced acute clinical symptoms such as headaches (34 respondents), coughs, and pain during urination (24 respondents). Chronic toxicity symptoms recorded included somatosensory disturbances in gold processing workers. Muscle cramps (17 respondents) and headaches (16 respondents) were the most common complaints among workers. Mercury level measurements showed that the average mercury level in workers’ urine was 207.6 µg/L. The mercury content in the studied urine samples exceeded the threshold Human Biomonitoring (HBM) set of 7 µg/L. The correlation testing indicated that mercury levels in urine correlated with several acute and chronic disease symptoms experienced by workers, such as ulcers (P value = 0.007), tongue swelling (P value = 0.007), olfactory loss (P value = 0.007), hearing disorders (P value = 0.007), and tremors (P value = 0.007). Based on the research findings, it can be concluded that more than half of the workers had mercury levels in their urine exceeding the threshold, and these mercury levels also correlated with several symptoms of diseases experienced by the workers.